THE RELATIONSHIP OF THE LEVEL OF KNOWLEDGE AND ATTITUDES OF PREGNANT WOMEN WITH THE INCIDENT OF HYPEREMESIS GRAVIDARUM IN PMB FITRIANI AM.KEB DUSUN 1 VILLA GESUKA BERAS PERBAUNGAN DISTRICT,SERDANG BEDAGAI DISTRICT, 2023 - sri eviani; Eva Ratna Dewi; Tetti Seriati Situmorang; Nopalina Damanik; Markus Doddy Simanjuntak; Febriyanti Panjaitan (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
Excessive nausea and vomiting during the day is a pregnancy complication that can affect a woman’s health and the growth and development of the fetus. Hyperemesis gravidarum is the medical term for this condition. These difficulties can be experienced and can be prevented during pregnancy (Syamsuddin, 2018). Research Design and Type This research uses a descriptive research design with a cross-sectional quantitative approach in which all variable data is examined simultaneously. Descriptive-quantitative research aims to explain or describe a social phenomenon without using statistical techniques or other quantification (measurements) to find relationships between variables. it was found that eight of the 42 respondents who had good knowledge did not experience hyperemesis gravidarum; six respondents (14.24 percent) and two respondents (4.76%). Apart from that, it was also stated that 34 respondents (81.00%) had poor information, especially 9 respondents (21.48%) had not experienced hyperemesis gravidarum and 25 respondents (59.52%) had experienced hyperemesis gravidarum. The Fisher Excat test with a value of p = 0.016 was used for statistical tests based on the Chi-Square test. It appears that there is a relationship between the prevalence of hyperemesis gravidarum in PMB Fitriani Am and the level of knowledge of pregnant women with p 5%, 0.016 0.05. Perbaungan District. In 2023, Serdang Bedagai. Pregnant women who have knowledge about hyperemesis gravidarum are better than pregnant women who have less knowledge.